The Comparative Theorizing about Infallibility of the Holy Prophet (PBUH) in Terms of Affecting Revelation - Mostafā Karimi; Sediqeh Parvān (پژوهش‌های تفسیر تطبیقی, 2021)
Received: 2020/5/7  |   Accepted: 2021/1/4One of the old arguments on the authenticity of Wahy (revelation) is whether it has been affected by the inner sentiments of the holy Prophet (PBUH) or not so based on this inappropriate thought, the opponents have considered the Qur’an a mixture of the word of God and human word. The present study aims to prove infallibility of the Prophet in terms of affecting Wahy and the Qur’an’s authenticity. Data collection is conducted using library method and data analysis is done through content analysis and comparative methodical thematic interpretation. Answering this argument is based on the 15th verse of Surah Yunus discussed in four important Shi’ite and Sunni exegetical books named “at-Tibyān”, “al-Mizān”, “Kashshāf”, and “Fi Zilāl al-Qur’an” all having a rationalist approach. These exegeses, in addition to making a reference to this verse as one of the traditional reasons for infallibility of the Prophet in terms of not affecting the Qur’an, have also referred to some rational arguments. The results of the study show that according to the four above exegeses, this holy verse implies the authenticity of Wahy and the prophet is infallible in terms of affecting that so there has not been any change, transformation, exchange, deletion, or addition in the Qur’an. The rational arguments focused by the commentators include “the prophet’s lack of ownership”, “divine ownership and taking this right away from the Prophet”, “God’s prudence and His creative power and science”, “the Prophet’s lack of power”, and “unity of power” that the last one seems to be more reliable.